Effect of Curing Methods on Compressive Strength of Sustainable Self-Consolidated Concrete. Issue 3 (February 2019) - Mohamed, Osama; Najm, Omar
Abstract: Concrete can only achieve the desired compressive strength and durability if cured properly for a prescribed period. For most building codes, concrete structural components and systems are designed for the 28-day compressive strength. Nonetheless, concrete structures are cured typically for only 3 to 7 days. There is an increasing use of curing techniques that involve chemical compounds such as acrylic-based compounds. The emergence of such techniques requires investigation of their effectiveness, compared to traditional curing methods. This article presents the findings of a study to compare the compressive strength of concrete cured using three methods, namely submersion in water, air curing under elevated temperature, and curing with a chemical compound. Compressive strength was determined on standard 150 mm x 150 mm x 150 mm cubes made of sustainable self-consolidated concrete (SCC) in which 90% of ordinary Portland cement content was replaced with combinations of high volume ground granulated blast furnace slag (GGBS), silica fume, and fly ash. A total of 20 mixes were tested, the first set of 10 mixes prepared with water to be binder (w/b) ratio of 0.33 and the second set of 10 mixes prepared with w/b of 0.36. For all mixes, samples cured under air with 45 °C temperature produced the highest 28-day compressive strength compared to other curing methods. Similarly, concrete samples cured using the chemical compound produced higher compressive strength compared to the traditional curing method. The sustainable SCC mix producing the highest compressive strength of 76.22 MPa under air curing was prepared with w/b of 0.33, 72.5% slag replacement ratio, 12.5% silica fume replacement ratio, 10% fly ash while Portland cement represented only 10% of the total binder content.